CEO Monitoring and Board Effectiveness: Resolving the CEO Compensation Issue - Ben Ali, Chiraz; Teulon, Frédéric (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
This study examines the impact of board governance mechanisms on the pay of Chief Executive Officers (CEOs) using a sample of major French listed companies for the 2009–2011 period. The results show that CEO pay is negatively associated with the presence of a family CEO and positively associated with board size, busy directors, board meetings, and compensation committee independence. We provide further evidence that CEO compensation increases with firm size, and both present and past performance. Our study casts doubt on the effectiveness of formal board attributes in constraining CEO compensation.